2016
DOI: 10.1007/s10620-016-4278-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Inflammatory Bowel Disease Research Registry Derived from Observational Electronic Health Record Data for Comprehensive Clinical Phenotyping

Abstract: Background Inflammatory bowel disease (IBD) is a heterogeneous collection of chronic inflammatory disorders of the digestive tract. Clinical, genetic, and pathological heterogeneity makes it increasingly difficult to translate efficacy studies into real-world practice. Our objective was to develop a comprehensive natural history registry derived from multi-year observational data to facilitate effectiveness and clinical phenotypic research in IBD. Methods A longitudinal, consented registry with prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…One study from North America demonstrated that UC is more common in the Hispanic population (26) . Several studies in the world have shown that even though UC is still the most prevalent IBD in some places, CD has been the most incident IBD (27,28) . In places with a higher incidence of IBD, the number of CD patients already surpasses that of UC patients (27,29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study from North America demonstrated that UC is more common in the Hispanic population (26) . Several studies in the world have shown that even though UC is still the most prevalent IBD in some places, CD has been the most incident IBD (27,28) . In places with a higher incidence of IBD, the number of CD patients already surpasses that of UC patients (27,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the world have shown that even though UC is still the most prevalent IBD in some places, CD has been the most incident IBD (27,28) . In places with a higher incidence of IBD, the number of CD patients already surpasses that of UC patients (27,29) . In our study, we noticed a small difference in the numbers of CD and UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Inflammatory Bowel Disease Center at the University of Pittsburgh Medical Center maintains a prospective natural history registry that tracks more than 3000 consented patients and has been described in detail. 13 Specific data are collected at the time of office encounters regarding disease activity (Harvey Bradshaw Index [HBI]) and behavior, quality of life (Short Inflammatory Bowel Disease Questionnaire), medication use, and health care use. Unless otherwise noted, medication use was defined as having at least one prescription for the drug in question during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…13 Briefly, IBD patients are consented and enrolled in a prospective, longitudinal, natural history registry, which organizes real world patient care data from 2009 to the present time. All data from the registry is derived from the electronic medical record and systematically processed and transformed for research.…”
Section: Materials and Methods And Designmentioning
confidence: 99%
“…13 All IBD related healthcare utilization including clinic visits, telephone encounters, hospitalizations, emergency room (ER) visits, and IBD related surgeries were derived from the IBD registry and temporally organized by calendar year. Healthcare utilization was also quantified by financial charges, which includes charge data for all healthcare services including, but not limited to, gastrointestinal care.…”
Section: Materials and Methods And Designmentioning
confidence: 99%